Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020 17th International Computer Conference on Wavelet Active Media Technology and Information Processing (ICCWAMTIP) 2020
DOI: 10.1109/iccwamtip51612.2020.9317337
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet-Based Cough Signal Decomposition for Multimodal Classification

Abstract: Signal classifications have benefited from the successes of ML and DNN architectures. Cough classification techniques mainly extract features such as the Mel Frequency CepstralCoefficients for training. Most of these works also focus on obtaining information from single data modalities. However, multimodal analysis has been shown to aggregate useful information from different modalities thereby improving the internal capacity of ML models at data analysis. In this research, we propose a multimodal cough data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…On a similar dataset, Coppock et al [22] report 0.85 AUC. Agbley et al [23] demonstrated a specificity of 0.81 at a sensitivity of 0.43 on a subset of COUGHVID dataset. Feng et al [24] used a subset of cough sounds from Coswara dataset and reported a performance of 0.90 AUC.…”
Section: Related Prior Work and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…On a similar dataset, Coppock et al [22] report 0.85 AUC. Agbley et al [23] demonstrated a specificity of 0.81 at a sensitivity of 0.43 on a subset of COUGHVID dataset. Feng et al [24] used a subset of cough sounds from Coswara dataset and reported a performance of 0.90 AUC.…”
Section: Related Prior Work and Contributionsmentioning
confidence: 99%
“…Laguarte et al [20] obtained AUC greater than 0.90 on samples from the COVID-19 Cough data set. These studies use acoustic feature representations of cough sounds such as Mel frequency cepstral coefficients (MFCCs) [18], Mel-spectrogram [20], [22], or scalograms [23], while the classifier models are deep learning based neural networks such as convolutional neural networks (CNNs) [23], recurrent neural networks (RNNs) [24], CNN based feature embeddings in support vector machines (SVM) [18] or with CNN based residual networks [20], [22]. There are also attempts at creating more controlled COVID-19 cough sound dataset from individuals in hospitals [25], [26].…”
Section: Related Prior Work and Contributionsmentioning
confidence: 99%
“…We adopt a three class diagnostic system previously created by Agbley et. al [2] -COVID-19 positive, symptomatic COVID-19 negative, and asymptomatic COVID-19 negative. Furthermore, by adding novel model features, we show that our model can better distinguish between COVID-19 positive patients and COVID-19 negative patients than any previous approaches, regardless of symptom status.…”
Section: B Ackgroundmentioning
confidence: 99%
“…In table 4.3, we compare the performance of our network in detecting COVID-19 to another deep learning model [2] trained on the COUGHVID dataset, along with medical experts' prediction performances. Our network outperforms both experts and Agbley et al [2] in detecting COVID-19 from cough audio files.…”
Section: R Esultsmentioning
confidence: 99%
See 1 more Smart Citation